How to Determine The Quality of Game-Based Media for Mathematics Learning? - Riska Ayu Ardani; Ariska Kurnia Rachmawati; Nilza Humaira Salsabila; Fitri Ayu Ningtiyas (FKIP Universitas Mataram, 2023)
Development research has become one of the popular studies in the 5.0 society era. Technological sophistication is a driving factor for educators and researchers to create shopisticated learning media. Technology-based learning media comes with their own uniqueness, one of which is game-based media (GBM). GBM has changed students’ perception that learning can be done by playing game. Before GBM is applied in the learning process, it is necessary to evaluate the media. This is intended so that GBM has good quality. GBM with high quality can improve its functions as a learning media. On the other hand, GBM can not only present an element of fun learning, but can also have a positive influence on the cognitive, affective, or psychomotor aspects of students. This literature review research provides theory for educators and other researcher to asses GBM. Overall, there are four aspects that need to be assessed in determining quality of game-based media, validity, practicality, effectiveness, and sophistication. Abstrak Riset pembangunan menjadi salah satu kajian yang populer di era masyarakat 5.0. Kecanggihan teknologi menjadi faktor pendorong bagi para pendidik dan peneliti untuk menciptakan media pembelajaran yang canggih. Media pembelajaran berbasis teknologi hadir dengan keunikan tersendiri, salah satunya adalah media berbasis game (GBM). GBM telah mengubah persepsi siswa bahwa belajar dapat dilakukan dengan bermain game. Sebelum GBM diterapkan dalam proses pembelajaran, perlu dilakukan evaluasi media. Hal ini dimaksudkan agar GBM memiliki kualitas yang baik. GBM dengan kualitas tinggi dapat meningkatkan fungsinya sebagai media pembelajaran. Di sisi lain, GBM tidak hanya dapat menghadirkan unsur pembelajaran yang menyenangkan, tetapi juga dapat memberikan pengaruh positif terhadap aspek kognitif, afektif, atau psikomotor siswa. Penelitian tinjauan pustaka ini memberikan teori bagi pendidik dan peneliti lain untuk menilai GBM. Secara keseluruhan, ada empat aspek yang perlu dinilai dalam menentukan kualitas media berbasis game, validitas, kepraktisan, efektivitas, dan kecanggihan.